Acute perforated appendicitis in a 15-day-old infant - Pham Nhu Hiep; Mai Trung Hieu; Nguyen Thanh Xuan; Huynh Thi Ngoc Kieu; Nguyen Huu Son (Elsevier, 2020)
Background: Even though no age is free to be affected by appendicitis, it is extremely rare in newborn infants. Clinical presentations are usually nonspecific, abdominal imaging is not always diagnostic, and definitive diagnosis is difficult. We present a 15-day-old infant with acute perforated appendicitis that was diagnosed and treated in our pediatric center. Case report: This case presented at Neonatal Intensive Care Unit with an 18-h-history of irritability, vomiting, and abdominal distension. With high white blood cell count and C-reactive protein level, the baby was initially diagnosed with neonatal sepsis. The ultrasound performed on day 3 after hospitalization found peritonitis but not seen appendicitis. Postoperative diagnosis confirmed acute perforated appendicitis with peritonitis. The baby was well covered without complication. Conclusion: This case highlights that preoperative diagnosis of acute appendicitis in neonates is difficult due to nonspecific clinical presentation and the extreme rarity of the disease.